#TITLE_ALTERNATIVE# - EGA NUGRAHA, NICO
The blasting process in Deep Ore Zone (DOZ) underground mining at production level, one of them is drawbell blasting. This blasting has done at some type of rock on this level, but this research is focused on forseterite magnetite skarn, and diorite. There is no significant problem in drawbell blasting if seen from distribution fragmen size. But if the fragment size compared to the grizlly size (80 x 80 cm), the fragment size is a long way off below grizzly size, so it is possible to optimize the drawbell blasting pattern. The objective of this research is to evaluate the pattern of drawbell blasting, analyse, and also determine distribution and fragmen size of drawbell blasting in forseterite magnetite and diorite, by using Split Desktop program and Kuz Ram Method. And also to optimize drawbell blasting pattern. Area of research cover the production level of Deep Ore Zone. The data input for Split Desktop program are taken from the field by taking the digital picture of rock fragment. And then the digital picture is processed by Split Desktop program, which is resulting the graph of distribution size of rock fragment. While Kuz Ram method is used to predict the blasting fragmentation. Based on Split Desktop meassurement, the drawbell blasting trial give influence of 80% fragment size increase, for forseterite magnetite skarn from the beginning 18,59 cm, becoming 20,09 cm for drawbell blasting pattern trial I, and become 29,76 cm for drawbell blasting pattern trial II. While at diorite give increase from beginning 25,27 cm, becoming 31,54 cm for drawbell blasting pattern trial I. This drawbell blasting trial also give influence of increasing the fragment top size, for forsiterite magnetite skarn from beginning 56,58 cm, becoming 68, 45 cm for drawbell blasting pattern trial I, and become 72,89 for drawbell blasting pattern trial II. While diorite give increase from beginning 68,04 cm, becoming 78,68 cm for drawbell blasting trial I pattern. The result during research give fragment size of drawbell basting pattern trial I for forseterite magnetite skarn, and for diorite, and also the drawbell blasting pattern trial II for forseterite magnetite skarn, still giving the fragment size below the grizzly size.